Love, comment, subscribe - Yardley, Cathy (Yardley, Cathy. Ponto Beach reunion., 2021)
"Back in high school, Lily Wang wanted to be popular, but she considered herself lucky to be part of a tight group of oddballs and honors students called the Nerd Herd. Now, at twenty-eight, she feels like she's finally on the cusp of succeeding as a beauty influencer-if she can hit five million subscribers, brands will take notice and she could get her own makeup line. Fellow Nerd Herd alum Tobin Bui has had a lot of success as a YouTube gamer. But the road to online stardom has been rocky. First, he disappointed his parents by dropping out of college, and now, after years of pranks, skits, and playthroughs, he's struggling to come up with new content to satisfy his ever-growing fan base. His agents say he needs cross-audience appeal, a new twist. When Nerd Herd frenemy Lily approaches Tobin about teaming up to do a video to bolster her brand and reinvigorate his, he agrees. But when their first collab video goes viral, their relationship heats up too. With the whole internet watching, will these two former misfits finally realize they're perfect together?"-Page 4 of cover.